Loading of halloysite nanotubes with BSA, α-Lac and β-Lg: a Fourier transform infrared spectroscopic and thermogravimetric study. (28th December 2016) - Duce, Celia; Della Porta, Valentina; Bramanti, Emilia; Campanella, Beatrice; Spepi, Alessio; Tiné, Maria Rosaria
Abstract: Halloysite nanotubes (HNTs) are considered as ideal materials for biotechnological and medical applications. An important feature of halloysite is that it has a different surface chemistry on the inner and outer sides of the tubes. This property means that negatively-charged molecules can be selectively loaded inside the halloysite nanoscale its lumen. Loaded HNTs can be used for the controlled or sustained release of proteins, drugs, bioactive molecules and other agents. We studied the interaction between HNTs and bovine serum albumin, α lactalbumin and β -lactoglobulin loaded into HTNs using Fourier transform infrared spectroscopy and thermogravimetry. These techniques enabled us to study the protein conformation and thermal stability, respectively, and to estimate the amount of protein loaded into the HNTs. TEM images confirmed the loading of proteins into HTNs.